The Role of Zakat, Infaq, Sadaqah (ZIS), HDI, and Government Expenditure on Poverty Alleviation: Economic Growth as an Intervening Variable - Kamarni, Neng; Utami, Yuli; Hasib, Fatin Fadhilah (Perhimpunan Intelektual Muslim Indonesia, 2024)
Zakat, Infaq, and Sadaqah are forms of instruments in Islam that are one of the tools in reducing poverty. Islam instructs its people not to feel that their property is theirs entirely, but in that property, there are rights for other people. This study aims to find out how the influence of ZIS (Zakat, Infaq, and Sadaqah), Human Development Index (IPM), and Government Expenditures on Poverty with Economic Growth as Intervening Variables in West Sumatra for the 2015-2020 period. This research is quantitative research using panel data. The data collection method is carried out by accessing reports that have been carried out by the Central Statistics Agency, and the West Sumatra Amil Zakat Agency (BAZNAS). The data that has been obtained is then processed using Structural Equation Modeling Partial Least Square. The research results show that ZIS and HDI have a negative relationship and a significant influence on poverty in West Sumatra. The important role of ZIS is proven in alleviating poverty if it is managed properly. Meanwhile, government spending has a positive and insignificant effect on poverty in West Sumatra. Government spending is meaningless if it is not accompanied by good planning and management.